Microbial perspective of multidisciplinary collaborative weight management approach: Ruminococcus gnavus may serve as a key target for weight loss - Sijia Zhao; Wenjun Wu; Wenyan Song; Qunyan Zhou; Haiyan Cheng; Shukun Deng; Jianxin Zhao; Hao Zhang; Wei Chen; Hongchao Wang (Gut Microbes)
Changes in the gut microbiota are associated with obesity and may influence weight loss. We are currently implementing a sustained multidisciplinary collaborative weight management (MCWM) approach to weight loss. We report significant improvements in participant health status after 6 months, along with alterations in the structure, interactions, and metabolic functions of the microbiota. We observed an enrichment of the gut symbiont Ruminococcus gnavus in obese subjects, which was significantly correlated with clinical indicators and contributed significantly to random forest (RF) classification, and revealed its correlation with bile acid metabolism. Experimental results indicate that R. gnavus impairs weight loss in diet-modified obese mice by altering the gut microbiota structure and influencing bile acid metabolism. The findings of this study highlight the significant role of the gut microbiota in obese patients and establishes a more substantial scientific foundation for the prevention and management of obesity.